Results 1 to 5 of 5

Math Help - The Binomial Theorem/Factorials?

  1. #1
    Junior Member
    Joined
    Jan 2009
    Posts
    26

    The Binomial Theorem/Factorials?

    Im a little confused on how to do this problem.

    Use the definition of [n] to show that [ 6 ] + [6] = [7] for all integers 1≤r≤6
    [r ] [r-1] [r] = [ r]

    The formula/definition is n!/r!(n - r!) am i correct? Help or an explanation of how to use this formula would be great! Thanks!!
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Master Of Puppets
    pickslides's Avatar
    Joined
    Sep 2008
    From
    Melbourne
    Posts
    5,236
    Thanks
    28
    firstly it is important to know that

     n! = n\times (n-1) \times (n-2) \times \cdots \times 3 \times 2 \times 1<br />

    for example 4! =4\times 3 \times 2 \times 1 \times = 24

    and 25! = 25 \times 24 \times \dots 3 \times 2 \times 1 \times = a massive number.

    For calculating \binom{n}{r} =\frac{n!}{r!(n - r!)}

    make sure you cancel as many terms as you can to make life easy

    i.e. \binom{6}{3} =\frac{6!}{3!( 6- 3!)}=\frac{6!}{3!( 3!)} =\frac{6\times 5\times 4\times 3!}{3!( 3!)} = \frac{6\times 5\times 4}{3!} = \frac{120}{6}= 20
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Junior Member
    Joined
    Jan 2009
    Posts
    26
    Quote Originally Posted by pickslides View Post
    firstly it is important to know that

     n! = n\times (n-1) \times (n-2) \times \cdots \times 3 \times 2 \times 1<br />

    for example 4! =4\times 3 \times 2 \times 1 \times = 24

    and 25! = 25 \times 24 \times \dots 3 \times 2 \times 1 \times = a massive number.

    For calculating \binom{n}{r} =\frac{n!}{r!(n - r!)}

    make sure you cancel as many terms as you can to make life easy

    i.e. \binom{6}{3} =\frac{6!}{3!( 6- 3!)}=\frac{6!}{3!( 3!)} =\frac{6\times 5\times 4\times 3!}{3!( 3!)} = \frac{6\times 5\times 4}{3!} = \frac{120}{6}= 20

    [6] + [6] = [7] for all integers 1≤r≤6.
    [r-1] [r] [r]

    I think i understand what your saying, however i am still confused as how to show the proof in the above statement...
    my work:
    6!/(r!-1(6-r!-1)) + 6!/(r!(6-r!)) = 7!/r!(7-r!)

    Is this the correct way of setting this up? If so, where do i go from here?
    Im confused, but thanks a lot for your time!
    Follow Math Help Forum on Facebook and Google+

  4. #4
    MHF Contributor
    Prove It's Avatar
    Joined
    Aug 2008
    Posts
    11,520
    Thanks
    1405
    Quote Originally Posted by Sxon View Post
    [6] + [6] = [7] for all integers 1≤r≤6.
    [r-1] [r] [r]

    I think i understand what your saying, however i am still confused as how to show the proof in the above statement...
    my work:
    6!/(r!-1(6-r!-1)) + 6!/(r!(6-r!)) = 7!/r!(7-r!)

    Is this the correct way of setting this up? If so, where do i go from here?
    Im confused, but thanks a lot for your time!
    Why don't you just evaluate \left(^6_r\right) for all r \in [1, 6]?


    Draw Pascal's Triangle and read off the 6th line... (the 1 on the top is the ZERO line...)
    Follow Math Help Forum on Facebook and Google+

  5. #5
    MHF Contributor
    Grandad's Avatar
    Joined
    Dec 2008
    From
    South Coast of England
    Posts
    2,570
    Thanks
    1
    Hello Sxon
    Quote Originally Posted by Sxon View Post
    Im a little confused on how to do this problem.

    Use the definition of [n] to show that [ 6 ] + [6] = [7] for all integers 1≤r≤6
    [r ] [r-1] [r] = [ r]

    The formula/definition is n!/r!(n - r!) am i correct? Help or an explanation of how to use this formula would be great! Thanks!!
    I think you mean to prove that \binom6r + \binom{6}{r-1}= \binom7r

    First, note that r! = (r-1)!\times r

    Then

    \binom6r + \binom{6}{r-1} = \frac{6!}{r!(6-r)!}+\frac{6!}{(r-1)!(6-r+1)!}

    = \frac{6!}{(r-1)!\times r\times(6-r)!}+\frac{6!}{(r-1)!\times(6-r)!\times (6-r+1)}

    = \frac{6!\times (6-r+1)}{(r-1)!\times r\times(6-r)!\times(6-r+1)}+\frac{6!\times r}{(r-1)!\times(6-r)!\times (6-r+1)\times r}

    = \frac{6!\times (6-r+1)+6!\times r}{(r-1)!\times(6-r)!\times (6-r+1)\times r}

    = \frac{6!(6-r+1+r)}{r!(6-r+1)!}

    = \frac{6!\times 7}{r!(7-r)!}

     = \frac{7!}{r!(7-r)!}

     =\binom7r

    Note that you can replace 6 throughout this proof by n, and get \binom{n}{r}+\binom{n}{r-1}= \binom{n+1}{r}

    Grandad
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Replies: 6
    Last Post: November 14th 2010, 12:51 PM
  2. binomial theorem
    Posted in the Algebra Forum
    Replies: 5
    Last Post: November 5th 2009, 05:53 AM
  3. Binomial Theorem or Binomial Coefficient
    Posted in the Pre-Calculus Forum
    Replies: 3
    Last Post: October 2nd 2009, 01:06 PM
  4. Binomial Theorem
    Posted in the Statistics Forum
    Replies: 3
    Last Post: July 16th 2009, 04:51 AM
  5. Binomial Theorem
    Posted in the Algebra Forum
    Replies: 1
    Last Post: May 27th 2008, 01:32 PM

Search Tags


/mathhelpforum @mathhelpforum